PENGARUH HARGA, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN JASA LAYANAN SERVICE, KEPUASAN PELANGGAN SEBAGAI VARIABEL MODERASI PADA PT. BIMA PERKASA SEJAHTERA - Anggraini, Mega (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study is (1) To determine the direct influence of price variables on the variable Decision to purchase services at PT. Bima Perkasa Sejahtera. (2) To determine the direct influence of promotion variables on the variable Decision to purchase services at PT. Bima Perkasa Sejahtera. (3) To determine the direct influence of customer satisfaction variables on the variable Decision to purchase services at PT. Bima Perkasa Sejahtera. (4) To determine the direct influence of satisfaction variables on the variable Decision to purchase services at PT. Bima Perkasa Sejahtera. (5) To determine the influence of Price and Promotion variables simultaneously on the variable Decision to purchase services at PT. Bima Perkasa Sejahtera. (6) To determine the influence of Price and service quality variables simultaneously on the variable Decision to purchase services at PT. Bima Perkasa Sejahtera. (7) To determine the influence of Promotion and service quality variables simultaneously on the variable Decision to purchase services at PT. Bima Perkasa Sejahtera. (8) To determine the influence of Price, Promotion and Service Quality variables simultaneously on the variable of service purchasing decisions at PT. Bima Perkasa Sejahtera. The theory used is the marketing mix theory and the theory of consumer behavior which are related to measuring behavior and persuasion. The method used in this study is a quantitative approach using a survey. The data analysis technique used is the Structural Equation Model. The results of the study show that price, service quality and customer satisfaction can influence purchasing decisions while promotions cannot influence purchasing decisions. Price, Service Quality and Promotion can influence Purchasing Decisions simultaneously. Not only that, customer satisfaction is known to moderate the influence between price and service quality on purchasing decisions but not between promotions and purchasing decisions.